2002
DOI: 10.1002/pon.551
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and affective dimensions of advanced cancer pain

Abstract: The present study was designed to explore the extent to which advanced cancer pain is explicable in terms of both physical pain intensity and affect. Most notably, it expanded on previous findings by more clearly elucidating the relationship between several discrete emotional states and the total experience of cancer pain. One hundred and eleven patients with cancer pain attending a Pain and Symptom Control Clinic were studied. Visual Analogue Scales (VASs) were used to quantify overall pain intensity and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 37 publications
1
28
0
1
Order By: Relevance
“…Another study by Sela et al investigated emotions elicited in response to cancer pain and found that there was a difference between emotions experienced by male and female patients. Both males and females experienced similar frustration and exhaustion, however a significant difference was found between the amounts of helplessness experienced, with females experiencing greater helplessness [12]. Gender differences were also observed in symptoms of fatigue [10,13,14].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Another study by Sela et al investigated emotions elicited in response to cancer pain and found that there was a difference between emotions experienced by male and female patients. Both males and females experienced similar frustration and exhaustion, however a significant difference was found between the amounts of helplessness experienced, with females experiencing greater helplessness [12]. Gender differences were also observed in symptoms of fatigue [10,13,14].…”
Section: Resultsmentioning
confidence: 87%
“…Gender difference in emotions, or changes in emotions, caused by advanced cancer was analyzed by multiple studies and found to be significant [10][11][12]. Carey et al found that terminally ill female cancer patients were in more positive moods [10].…”
Section: Resultsmentioning
confidence: 99%
“…Other unknown factors that might be influencing anxiety have to be explored. Cancer pain is known to be a multidimensional construct consisting of sensory and emotional components, with the emotional component of pain above the sensory 14 . It might be speculated that analgesic medications alleviate sensory pain, leaving the elevated emotional pain.…”
Section: Discussionmentioning
confidence: 99%
“…As pain treatment had often failed during the course of their disease, there were patients who had lost confidence in health care professionals and even ceased to believe that pain relief was achievable. Each acute pain episode they had gone through may have elevated their levels of frustration and increased the physical-sensory pain (Sela et al 2002), contributing to difficulties with improving pain relief later in the course of cancer. Lack of knowledge and skill concerning pain management among health care professionals may still be the reason for not taking pain seriously (Strang 1998).…”
Section: Trustmentioning
confidence: 99%
“…Despite the demonstrated efficiency of these approaches, cancer-related pain is not adequately managed and too many patients still suffer from unrelieved pain (Thomason et al 1998, Sela et al 2002. The pain experience is the end result of a complex process, one that occurs at various levels.…”
Section: Introductionmentioning
confidence: 99%